2010
DOI: 10.2478/v10001-010-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the activity of oxidative enzymes in the tissues of male wistar albino rats exposed to cadmium

Abstract: Objective: The objective of the present study was to investigate the effect of cadmium (Cd) on the activities of some oxidative enzymes [viz Aldehyde oxidase, AO (E.C. 1.2.3.1); Xanthine oxidase, XO (E.C. 1.2.3.2); Sulphite oxidase, SO (E.C.1.8.3.1.); and Monoamine oxidase, MO (E.C. 1.4.3.4)] in the liver and kidney. Materials and methods: Male Wistar albino rats were administered 1, 2 and 4 mg Cd 2+ /kg body weight for one and three months. The activities of the oxidative enzymes were subsequently analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…7). The graphical outcomes of the present study conformed with previous reports, showing that exposure to Cd results in elevated levels of MDA, a derivative of lipid peroxidation and biomarker of oxidative damage [10,49,50]. Again, the results proposed that the leaf extract of A. vogelii ameliorated Cd-initiated oxidative stress through enhancement of enzymatic antioxidant defence system in male Wistar rats (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…7). The graphical outcomes of the present study conformed with previous reports, showing that exposure to Cd results in elevated levels of MDA, a derivative of lipid peroxidation and biomarker of oxidative damage [10,49,50]. Again, the results proposed that the leaf extract of A. vogelii ameliorated Cd-initiated oxidative stress through enhancement of enzymatic antioxidant defence system in male Wistar rats (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…Yousef et al (2008) indicated that body weight reduction can be used as an important indicator for the deterioration of rat general health status. Cadmium has inhibitory action on digestive and absorption enzymes (Asagba, 2010). This finding may explain the weight loss of rats as observed in this experiment.…”
Section: Discussionsupporting
confidence: 72%
“…Its intracellular accumulation induces oxidative stress leading to hepatocellular damage via displacement of redox-active metals, depletion of redox scavengers, inhibition of anti-oxidant enzymes and inhibition of the electron transport chain resulting in mitochondrial damage (Nair et al, 2013;Adiele et al, 2012;Patra et al, 2011). In the present study, the significant decrease in the serum total protein and albumin of animals exposed to cadmium can be attributed to impairment in hepatocyte functions causing decreased cytochrome P-450 activity and inhibition in protein metabolism in the liver (Ibiam et al, 2013;Asagba, 2010). Whereas, the increased serum level of direct bilirubin and total bilirubin in the present study is a clear indication of hepatic dysfunction which correlates with the oxidative damage in the liver due to oxidative stress (Renugadevi and Prabu, 2010;Kowalczyk et al, 2003).…”
Section: Discussionmentioning
confidence: 99%